(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Kupipakva rasayana are unique pharmaceutical procedure in the field of Rasashastra where in Mercury along with other minerals and metals are sublimated by subjecting it to gradual increase in temperature for specific time. They are more potent and quick acting even in smaller dose. Tamra Sindoora is one such Kupipakva Rasayan which is not that much popular and widely used in daily practice. But it is having a wide range of therapeutic utility. It is a combination of Parada (mercury), Gandhaka (sulphur) and Tamra (copper) in the ratio of 1:1:1/2. Chemistry itself includes the determination of chemical and biological incompatibilities among the various ingredients of a prescription. Here we will come to know about various synthetic methods by which natural substances are converted into products with more favourable therapeutic or pharmaceutical properties. In the present paper will discuss about probable chemistry of Tamra Sindoora.